The transatlantic slave trade : a history - Rawley, James A. (New York : Norton, 1981)
A study of slave trade between the 15th to 19th centuries covering the economics, demography, epidemiology, and politics of the trade.
The early years of the slave trade -- The Portuguese pioneers -- Spain and the slave trade -- The Dutch and the Danes -- France: the early years -- France in the eighteenth century -- England gains ascendancy -- Bristol -- Liverpool -- London and the eighteenth-century slave trade -- The economics of the slave trade -- The middle passage -- Americans enter the slave trade -- The American dimensions and the Massachusetts contribution -- Rhode Island -- The American slave market.
Includes bibliographical references and index.
Self-Renewing
NLJCols20082021
Keywords: Slave trade -- History; Slave trade; Sklavenhandel; Geschichte; Slavenhandel; Slave trade -- History; Geschichte 1434-1870.; Geschichte 1434-1870; Africa -- Slave trade with America, to ca 1850; America -- Slave trade with Africa, to ca 1850; History